The Effectiveness of the Siriraj Stroke Score (SSS) and National Institute of Health Stroke Scale (NIHSS) Assessment Methods in Determining the Actual Nursing Diagnosis of Stroke Patients in the Emergency Room - M Sobirin Mohtar; Subhannur Rahman; Ahmad Apriannor; Gustin Restu Auliyah (Poltekkes Kemenkes Semarang, 2022)
Background: stroke is a disease of the brain in the form of focal nerve function disorders caused by disruption of blood circulation to the brain and causing symptoms in the form of neurological deficits. As the number of stroke patients increases, the assessment needs to focus on neurology and is an emergency.Purpose: analyzing the effectiveness of the assessment method NSSS and NIHSS in determining the number of diagnoses actual nursing and the speed of time to determine the diagnosis of stroke patients in the Emergency Room.Methods: this study used a pre-experimental approach. Theerty sample were used from a new patient with a medical diagnosis of stroke, while the sampling technique in this study was accidental sampling. Data collection on each sample was directly carried out using two assessment methods. The SSS assessment consists of 5 components and the NIHSS 11 components. Data analysis used sperm correlation and correlation coefficient interpretation test.Results: the results of the sperm correlation test in the SSS and NIHSS methods both show p=0.000. The level of closeness were analyzed using the correlation coefficientthere is a very strong relationship is NIHSS to the length of the duration of determination (r = 0.858).Conclusion: the SSS and NIHSS assessment methods are effective in establishing the diagnosisactual nursingin stroke patients in the Emergency Department, however, in terms of duration of assessment and determination of the number of diagnoses, SSS is more effective, while from the duration of determining nursing diagnoses, NIHSS is more effective.